How Family Assistance Teams Support Maternal-Child Nutrition Behavior Change for Stunting Prevention: A Qualitative Comparative Case Study in Kampar Regency, Indonesia - Mitra, Mitra; Rany, Novita; As Syifa, Ervira Dwiaprini; Dewi, Oktavia (Journal of Current Health Sciences, 2026)
Stunting is a chronic nutritional problem with long-term impacts on child development and future productivity. The Family Assistance Team (FAT) plays a crucial role in community-based interventions by providing education and mentoring to at-risk families. This study aims to explore the role of FAT in supporting behavioral changes to prevent stunting in maternal and child nutrition. A qualitative case study approach was used. The primary informants, including FAT members and supporting informants, were the Head of the Community Health Center, nutritionists, the Head of Population Control, field coordinators for the Family Planning Program, and mothers of children under five years old. Purposive sampling was employed to select informants. Data were gathered through in-depth interviews, Focus Group discussions, and document review. Data validity was ensured through source and method triangulation. Thematic analysis was used to identify key findings. Five major themes emerged: (1) FAT’s role in health education and growth monitoring; (2) collaboration across programs; (3) risk factors for stunting; (4) challenges in mentoring; and (5) behavioral changes in mothers and children. FAT reported changes in mothers' behavior, particularly in toddler feeding patterns, which were supported through regular monitoring using WhatsApp messaging. However, program implementation still faces various obstacles, requiring capacity building for cadres, policy support, and cross-sector collaboration to ensure the sustainability of the stunting reduction program. Abstrak. Stunting adalah masalah gizi kronis yang berdampak jangka panjang terhadap perkembangan anak dan produktivitas di masa depan. Tim Pendampingan Keluarga (TPK) memainkan peran penting dalam intervensi berbasis masyarakat melalui pendidikan dan pendampingan keluarga berisiko. Penelitian ini bertujuan untuk mengeksplorasi peran TPK dalam mendukung perubahan perilaku terkait gizi ibu dan anak untuk mencegah stunting. Pendekatan studi kasus kualitatif digunakan dalam penelitian ini. Informan utama yaitu TPK dan informan pendukung terdiri dari Kepala Puskesmas, ahli gizi, Kepala Pengendalian Penduduk, koordinator lapangan Program Keluarga Berencana, dan ibu balita. Teknik pengambilan sampel menggunakan purposive sampling. Data dikumpulkan melalui wawancara mendalam, Fokus Grup Diskusi, dan tinjauan dokumen. Validitas data melalui triangulasi sumber dan metode. Analisis tematik digunakan untuk mengidentifikasi temuan kunci. Lima tema utama yaitu: (1) peran TPK dalam pendidikan kesehatan dan pemantauan pertumbuhan; (2) kolaborasi lintas program; (3) faktor risiko stunting; (4) tantangan dalam pendampingan; dan (5) perubahan perilaku ibu dan anak.   TPK melaporkan adanya perubahan perilaku ibu, khususnya dalam pola makan balita, yang didukung melalui pemantauan rutin menggunakan media perpesanan WhatsApp. Namun demikian, implementasi program masih menghadapi berbagai hambatan, sehingga diperlukan penguatan kapasitas kader, dukungan kebijakan, serta kolaborasi lintas sektor guna menjamin keberlanjutan program penurunan stunting.